Supramolecular Organogelation of Bacteriochlorophyll‐c Possessing an Isobutyl Substituent at the 8‐Position in Carbon Tetrachloride. Issue 4 (10th November 2016) - Mizoguchi, Tadashi; Kinoshita, Yusuke; Harada, Jiro; Tamiaki, Hitoshi
Abstract: The supramolecular organogelation of bacteriochlorophyll(BChl)‐ c carrying an isobutyl substituent at the 8‐position was observed in carbon tetrachloride at a concentration of about 10 mm at room temperature. The BChl‐ c gel was evaluated by several spectroscopic measurements: the electronic absorption spectrum exhibited a far‐red shift of the Qy‐absorption from 660 to 748 nm and the FTIR spectrum showed a shorter frequency shift of the 13‐C=O stretching from 1683 to 1643 cm −1 compared to the shifts of the corresponding monomer solution in tetrahydrofuran. These observations strongly indicate that the gelating BChl‐ c molecules form self‐aggregates that are reminiscent of light‐harvesting chlorosomes of green photosynthetic bacteria. The present supramolecular organogel prepared from natural chlorophylls is promising for the creation of an intelligent soft material involving artificial photosynthesis. Abstract : Getting organized : The supramolecular organogelation of bacteriochlorophyll (BChl)‐ c was investigated. A BChl‐ c derivative possessing an isobutyl group at the 8‐position and (3 1 S )‐configuration (S[I, E]BChl‐ c ) gelated CCl4 at room temperature. R[E, E]BChl‐ c, which bears an ethyl group at C8 and (3 1 R ) stereochemistry, did not. The gelating S[I, E]BChl‐ c self‐aggregated in CCl4 in a similar manner as natural light‐harvesting chlorosomes (see figure).